SUSPECTED OF TRANSMISSIBLE GASTROENTERITIS AND COLIBACILLOSIS IN PIGLET AT TEGAL SUCI VILLAGE FARM, SEBATU DISTRICT, GIANYAR REGENCY, BALI - Shafira Laili Aulia; I Ketut Suarjana; Ida Bagus Oka Winaya; Gusti Ayu Yuniati Kencana; I Made Dwinata (Buletin Veteriner Udayana, 2024)
The case pig originated from a farm in Tegal Suci Village, Sebatu District, Gianyar Regency, Bali. This case study review aims to establish the diagnosis of death in a 45-day-old female pig using anamnesis, epidemiological history, clinical symptoms, anatomical pathology examination, histopathology, and laboratory tests. The observed symptoms in the case pig included anorexia, weakness, and diarrhea. Necropsy results showed hemorrhaging in almost all organs of the case pig. Histopathological examination revealed lesions in the intestine, suggesting a Transmissible Gastroenteritis Virus (TGEV) infection, specifically intestinal villous atrophy. Bacteriological examination successfully isolated Escherichia coli bacteria in the lungs, liver, and heart. Fecal examination in the parasitology laboratory showed no evidence of worm eggs or protozoan infections. Based on a series of tests conducted, it can be concluded that the case pig is suspected to have been infected with TGEV and E. coli. Further testing is needed to investigate the co-infection of Transmissible Gastroenteritis Virus and E. coli in pigs to determine the appropriate treatment for severe diarrhea in pigs.